(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Saccharum spontaneum L. known as Kasa (Family: Poaceae) is a traditional herb, it has excellence medicinal value; has been advocated in the treatment gynaecological troubles, respiratory disease. Roots are used as galactagogue and diuretic and in ayurveda system roots are also used as astringent, emollient, refrigerant, diuretic, purgative, tonic, aphrodisiac and useful in treatment of dyspepsia, burning sensation, piles and sexual weakness. Various parameters like macroscopy, microscopy, fluorescence analysis as well as extractive value and quantitative phytochemical screening of different extractives were studied. The major components of the extractives like total phenolic, total flavonoids were also estimated respectively. The characteristic of microscopy, physicochemical, fluorescence analysis and quantitative chemical screening were performed in root extractives of the plant material as a mean of authentication.